Processo para Incorporação do Conceito de Dívida Técnica de Requisitos em Projetos Acadêmicos - Guilhermino, Fernando; Lencastre, Maria; Castro, Jaelson (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3539, 2024)
Although the concept of Technical Requirements Debt (DTR) is present in research and is applied in practice, its use in classroom projects is still restricted. An open question is, “How can we bring academic experience closer to the job market in Requirements Engineering (RE) activities, providing a realistic understanding of professional challenges?” This paper aims to define a process to incorporate DTR into academic projects, aligning the student experience with the professional environment. To achieve our objective, we conducted ad hoc bibliographic research and a survey; then, we proposed a process and ran classroom experiments. The results show that the proposed process is helpful in RE disciplines and provides an enriching experience. It promotes the understanding and practical application of DTR, helping to identify its elements in projects, but it still requires more studies.